STUDY ON MODULAR HOUSES DESIGN - Carmen Marza; Georgiana Corsiuc; Ana Maria Graur (Journal of Industrial Design and Engineering Graphics, 2019)
In the field of civil engineering, in the last period emerged and developed the idea of modular constructions, which is in consensus with the alert rhythm of the present times that we are going through, while responding to the requirement of economic efficiency. In this paper the authors present a project for some modules that can be assembled in several ways so that according to the destination and the requirements of the clients they can be personalized to meet their needs and expectations. Obviously, special attention has been paid to the technology of joining modules, solving the covering surfaces and other execution details required to ensure comfort in the habitat area.